2015
DOI: 10.1007/s11356-015-5813-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus on chemical forms of Cd in plants of four spinach (Spinacia oleracea L.) cultivars differing in Cd accumulation

Abstract: 14In order to clarify how cadmium (Cd) chemical forms in planta relate to the genotype difference 15 in Cd accumulation of spinach (Spinacia oleracea L.), two low-Cd and two high-Cd cultivars 16 were compared under a hydroponic experiment with two concentrations of Cd (1 or 5 mg Cd L -1 ). 17The concentrations of phosphorus in the hydroponic system were also adjusted to two levels tested cultivars and the effect had superiority over the cultivar alternation under higher Cd stress. 24Cadmium in the NaCl-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 44 publications
2
9
1
2
Order By: Relevance
“…The chemical form of Cd determines the characteristics of Cd migration, potential phytotoxicity, and accumulation in plants and then influences the detoxification and tolerance to Cd of plants [10][11][12][13]. Yin et al [12] found that the different capacity to binding Cd different forms (such as F HCl -Cd and F r -Cd) played an important role in the genotype difference in Cd accumulation of spinach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical form of Cd determines the characteristics of Cd migration, potential phytotoxicity, and accumulation in plants and then influences the detoxification and tolerance to Cd of plants [10][11][12][13]. Yin et al [12] found that the different capacity to binding Cd different forms (such as F HCl -Cd and F r -Cd) played an important role in the genotype difference in Cd accumulation of spinach.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [12] found that the different capacity to binding Cd different forms (such as F HCl -Cd and F r -Cd) played an important role in the genotype difference in Cd accumulation of spinach. Mwamba et al [14] demonstrated that metals which are both in the form of insoluble phosphate and firmly adsorbed in the cell walls and vacuoles are not free to migrate and have low toxicity, whereas Xu et al [15] reported that high Cd mobility is often in the forms of the water soluble Cd, inorganic Cd, and Cd complexes with organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…When P is deficient, plant growth and crop yield are reduced, as P is an essential element for the synthesis of nucleic acids, phospholipids, and adenosine triphosphate (ATP) (Yin et al, 2016). Our results indicated that there was a significant negative correlation between Cd, Pb, or Zn and P concentration in water spinach plants (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…The plant samples were heated at 105°C for 30 min, dried at 60°C for 24 h, mulled and sieved through a 2-mm nylon mesh and reserved in a glass bottle. The As, Cd and Zn concentrations in the plants were determined by HNO 3 -HClO 4 digestion in a conical flask (Simmons et al 2005;Yin et al 2016).…”
Section: Methodsmentioning
confidence: 99%